Discontinuation of secondary prophylaxis against penicilliosis marneffei in AIDS patients after HAART - Chaiwarith R. (2014)
A retrospective cohort study was conducted to determine the relapse rate of penicilliosis marneffei after the discontinuation of itraconazole secondary prophylaxis in 33 HIV-infected patients who received HAART and had CD4 cell counts of 100 cells/μl or greater for at least 6 months. The observed incidence of relapse of penicilliosis marneffei was zero cases per 641 person-months (95% confidence interval 0-0.6 cases per person-month) after a median follow-up of 18 months (range 6-45). © 2007 Lippincott Williams & Wilkins.